"Commentary: Research, Redskins, and Reality." - Deloria, Jr., Vine (American Indian Quarterly)
Comments on observations and reflections of a personal nature on the present state of Indian-scholar/researcher relations. Author's complaints against researchers; Shortcomings of the research done by writers Ruth Beebe Hill and Peter Mattheissen on the issue of Indian lifestyle; Indians at a great disadvantage due to misrepresentations written about their culture; A new vehicle for Indian/scholar communication; More.